2019
DOI: 10.1101/cshperspect.a038398
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of the Influenza Virus Transcription and Replication Machinery

Abstract: Transcription and replication of the influenza virus RNA genome is catalyzed by the viral heterotrimeric RNA-dependent RNA polymerase in the context of viral ribonucleoprotein (vRNP) complexes. Atomic resolution structures of the viral RNA synthesis machinery have offered insights into the initiation mechanisms of viral transcription and genome replication, and the interaction of the viral RNA polymerase with host RNA polymerase II, which is required for the initiation of viral transcription. Replication of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 85 publications
0
100
0
Order By: Relevance
“…Polymerase activity requires multiple steps for successful replication and transcription, beginning with protein expression, trimer assembly, RNA binding, RNP assembly, and ultimately the synthesis of new RNA products [ 39 ]. Primer extension reports on the cumulative success of this process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymerase activity requires multiple steps for successful replication and transcription, beginning with protein expression, trimer assembly, RNA binding, RNP assembly, and ultimately the synthesis of new RNA products [ 39 ]. Primer extension reports on the cumulative success of this process.…”
Section: Resultsmentioning
confidence: 99%
“…The influenza polymerase performs diverse functions as transcription peaks early in infection, followed by production of the replication intermediate cRNA, and ultimately the final replication product vRNA [ 23 ]. The different functions are achieved in part by discrete conformations of the viral polymerase [ 39 , 41 ]. All of these require appropriate binding and positioning of the template [ 21 , 34 , 36 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…33 It has been suggested that ANP32A plays a role in assembly or regulation of this dimerization process, for example, by recruitment of a second polymerase to apo polymerase for the formation of viral RNPs. 37 In this context the polyvalent nature of the interaction between ANP32A and 627-NLS may be of functional relevance. In particular, the more extensive effective capture radius of the IDD of avANP32A may be important.…”
Section: Discussionmentioning
confidence: 99%
“…Cap snatching is carried out by the RdRp utilizing the PB2 cap-binding domain (residues 320-485) and the PA endonuclease (residues 1-196). The 10-to 15-nt capped host RNA fragments are then used as primers for transcription of viral mRNA (for review, see Fodor and te Velthuis 2019;Wandzik et al 2020).…”
Section: Transcriptionmentioning
confidence: 99%
“…Additional adaptations are believed to counteract mammalian antiviral immune pathways. The retinoic acidinducible gene 1 protein (RIG-I) recognizes influenza vRNA on the basis of a 5 0 -terminal triphosphate moiety and an adjacent patch of double-stranded RNA (dsRNA) that is the viral promoter binding the RdRp (for review, see Fodor and te Velthuis 2019;Wandzik et al 2020). During infection, the viral NS1 protein counteracts RIG-I, which would otherwise result in the induction of interferon (IFN) and IFN-stimulated gene (ISG) expression, such as MX1, protein kinase R (PKR), and IFITM3 (Pichlmair et al 2006;Rehwinkel et al 2010;Rajsbaum et al 2012).…”
mentioning
confidence: 99%